The Mediating Role of Cognitive Emotion Regulation in the Relationship between Cognitive Flexibility and Psychological Well-Being - Kiye, Semra; Çiçek, Ecem (My University, 2024)
This study investigates the mediating role of cognitive emotion regulation in the relationship between cognitive flexibility and psychological well-being. The research was conducted using a relational scanning model with 312 students from various universities. 216 of the participants are women and 96 are men, aged between 18 and 55. Among them, 53 were in their first, 34 in their second, 87 in their third, and 138 in their fourth year of study. The research instruments included the Psychological Well- Being Scale, Cognitive Flexibility Inventory, and Cognitive Emotion Regulation Scale. Regression-based bootstrapping was used to analyze the data, and positive, statistically significant relationships were found between cognitive flexibility, psychological well-being, and adaptive sub-dimensions of cognitive emotion regulation. Furthermore, the indirect effect of cognitive emotion regulation on the cognitive flexibility- psychological well-being link was found to be significant. Specifically, refocus on planning, positive refocusing, and positive reappraisal sub-dimensions exhibited a partial mediating role in this relationship, whereas the mediating role of the putting into perspective sub-dimension was not supported. In conclusion, as levels of cognitive flexibility increase, concurrent rises in cognitive emotion regulation are observed, thereby contributing to enhanced psychological well-being.
Keywords: Psychological Well-Being, Cognitive Flexibility, Cognitive Emotion Regulation